Abdominal Vascular Injuries - Hoshina, Katsuyuki; Miyata, Tetsuro; Miyahara, Takuya; Akagi, Daisukem; Hosaka, Akihiro; Okamoto, Hiroyuki; Kanetaka, Takehito; Kondo, Keisuke; Shigematsu, Kunihiro; Nakazawa, Tatsu; Saito, Takehito; Yamamoto, Kota (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2004)
Although their incidence is rare, successful management of injuries to the abdominal aorta and its main branches is a challenge to both trauma surgeons and vascular surgeons. Early diagnosis is extremely important and surgical exploration should be performed without delay. A thorough knowledge of the abdominal vascular anatomy and techniques of vascular repair are indispensable together with the concept of damage control surgery, the principle of abbreviated laparotomy with planned reoperation. The primary goal in the management of these patients should be hemorrhage control rather than maintenance of blood flow to save their lives.